The "open innovation" paradigm: A contingency perspective - Marko T. Torkkeli; Carl Joachim Kock; Pekka A. S. Salmi (Journal of Industrial Engineering and Management (JIEM), 2009)
The "open innovation" model is currently being touted as a superior path for achieving long-term success. Rather than relying on their own, limited resources for research and development in the traditional, closed invention system, firms are encouraged to share knowledge across firm boundaries to enhance their innovative potential. Yet, such sharing may also have adverse consequences by reducing the rarity of a firm's inventions. This paper accordingly attempts to identify and analyze the parameters that determine whether open or closed types of innovation management are most appropriate for a given firm. Following a contingency perspective, we examine these determinants as various internal and external constraints (situational factors). More specifically, applying concepts related to absorptive capacity, complementary resources, game theory and others, we derive testable propositions and provide case study evidence regarding the value generating properties of open innovation
Keywords: 650; open innovation; R&D; competitive advantage; resource-based view